2021
DOI: 10.3389/fendo.2021.693004
|View full text |Cite
|
Sign up to set email alerts
|

Catecholaminergic Crisis After a Bleeding Complication of COVID-19 Infection: A Case Report

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) presents in some cases with hemostatic and thrombotic complications. Pheochromocytomas are unusual, though potentially lethal tumors. Herein we describe the first case of hemorrhage in a pheochromocytoma related to SARS-CoV-2 infection. A 62-year-old man consulted for syncope, fever, and palpitations. He was diagnosed with SARS-CoV-2 pneumonia and presented with a hemorrhage in a previously unknown adrenal mass, which resulted in a catecholaminer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 19 publications
(34 reference statements)
0
11
0
Order By: Relevance
“…Importantly, our patient was completely normotensive, and apart from sweating, not all the other symptoms would certainly arouse suspicion of PCC. While clinicians often put too much emphasis on the presence of hypertension, the absence of a positive history of hypertension in our patient might have contributed to the lack of suspicion of a catecholamine-producing tumor, hindering the timely treatment of this potentially life-threatening tumor ( 11 , 12 ).…”
Section: Discussionmentioning
confidence: 93%
“…Importantly, our patient was completely normotensive, and apart from sweating, not all the other symptoms would certainly arouse suspicion of PCC. While clinicians often put too much emphasis on the presence of hypertension, the absence of a positive history of hypertension in our patient might have contributed to the lack of suspicion of a catecholamine-producing tumor, hindering the timely treatment of this potentially life-threatening tumor ( 11 , 12 ).…”
Section: Discussionmentioning
confidence: 93%
“…Adrenal hemorrhage has been exceptionally described in relationship with medulla; a first case of pheochromocytoma-related hemorrhage in a 62-year-old male admitted for coronavirus-associated pneumonia was the initial sign that led to the detection of the adrenal tumor [87].…”
Section:  Discussionmentioning
confidence: 99%
“…We also reviewed all the articles published from 2005 to 2022 in PubMed, dedicated to adrenal bleeding with known results of urinary or plasma catecholamines or metanephrines (8,10,12,14,16,17,24,. The analysis showed that catecholamines or metanephrines (plasma or urine) were elevated in 38.9% of patients with adrenal bleeding without pheochromocytoma.…”
Section: Discussionmentioning
confidence: 99%
“…Phenoxybenzamine and doxazosin are the most commonly used. The main differences between those two drugs concern selectivity (8,10,12,14,16,17,24,.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation